An Undeserved Gift from God: Conservative Christian Experiences of Divine Grace - Snow, Lindsay M. (Journal of psychology and theology, 2023)
The reception of God’s grace is a salient spiritual experience and is one that lies at the heart of Christianity. The present study sought to address a gap in the psychological literature pertaining to the experience of divine grace among Protestant Christians in a qualitative study with 30 adult self-identified Protestant Christians. By using Strauss and Corbin’s grounded theory data analysis, themes emerged to reveal how these Christians conceived of and experienced grace. Specifically, results indicated that these Christians most often spoke of “undeservedness” as the primary characteristic from which all other conceptions of grace flowed. The notion of grace being God’s undeserved gifts framed four important dimensions of the conservative Protestant understanding and experience of grace: (a) it specified components of salvific grace, (b) it identified an ongoing grace, (c) it cultivated specific outcomes, and (d) it highlighted distinct obstacles that make it difficult to grasp God’s grace. These findings expand the current body of literature regarding religiosity in that they highlight the primacy of divine grace as central to the religious experience of conservative Christians.